Elevation of Fasting Ghrelin in Healthy Human Subjects Consuming a High-Salt Diet: A Novel Mechanism of Obesity? - Yong Zhang (Nutrients, 2016)
Overweight/obesity is a chronic disease that carries an increased risk of hypertension, diabetes mellitus, and premature death. Several epidemiological studies have demonstrated a clear relationship between salt intake and obesity, but the pathophysiologic mechanisms remain unknown. We hypothesized that ghrelin, which regulates appetite, food intake, and fat deposition, becomes elevated when one consumes a high-salt diet, contributing to the progression of obesity. We, therefore, investigated fasting ghrelin concentrations during a high-salt diet. Thirty-eight non-obese and normotensive subjects (aged 25 to 50 years) were selected from a rural community in Northern China. They were sequentially maintained on a normal diet for three days at baseline, a low-salt diet for seven days (3 g/day, NaCl), then a high-salt diet for seven days (18 g/day). The concentration of plasma ghrelin was measured using an immunoenzyme method (ELISA). High-salt intake significantly increased fasting ghrelin levels, which were higher during the high-salt diet (320.7 ± 30.6 pg/mL) than during the low-salt diet (172.9 ± 8.9 pg/mL). The comparison of ghrelin levels between the different salt diets was statistically-significantly different (p < 0.01). A positive correlation between 24-h urinary sodium excretion and fasting ghrelin levels was demonstrated. Our data indicate that a high-salt diet elevates fasting ghrelin in healthy human subjects, which may be a novel underlying mechanism of obesity.